Capital Flows in a Transitional Economy and the Sterilization Dilemma : The Hungarian Case - Siklos, Pierre (IMF Working Papers; Working Paper, 1996)
This paper compares Hungary's experience with sterilization with that of other capital inflow episodes. The study focuses on the short-run impact of sterilization on monetary policy. The empirical data indicate that sterilized interventions by the National Bank of Hungary (NBH) were not significant until mid-1994, sometime after the return to power of the former Communist leaders. Thus, in the second half of 1994, the NBH began to demonstrate more firmly its independence by tightening monetary policy. By the beginning of 1995, the direction of fiscal policy had begun to show consonance with the overall aims of monetary policy.